A eficácia jurídica dos deveres no contexto do Estado Democrático de Direito - Marcilio, Thiago Gomes (2020)
This dissertation predisposes to analyze the historical abandonment of duties, taking as its starting point the French Revolution and following the trajectory of these in the twentieth century, already in the context of the Social Rule of Law, through a historical-bibliographical approach. Secondly, using a zetetic methodology, we will seek to formulate a categorization of duties, so that its operational structure, including the analysis of the possibility of setting an Original Duty, which could serve as a guide to the structuring of such duties. To this end, the subjects of duty and the relativization in the fulfillment of these same duties from one subject to another will be delineated. The research also proposes to dialogue with constitutional and infraconstitutional rules in the search for the effectiveness of duties